English Language Classroom Anxiety and Performance of Senior High School Learners - KABIGTING, RYAN; Nanud, Joy Ann (International Journal of Linguistics and Translation Studies, 2020)
The study applied quantitative research method which aimed at describing the effect of English Language Classroom Anxiety to the grades of male and female Grade 12 Humanities and Social Sciences leaners. Adapted questionnaire was used as the main source in the data collection. This was evaluated by a teacher of English to meet the objectives of the study. The gathered data were analyzed and interpreted using mean, standard deviation, Chronbach’s coefficient alpha and Pearson r. The study revealed that the mean grade of the respondents was very satisfactory; the level of anxiety of the respondents was neutral; the male and female levels of anxiety were both interpreted neutral; the degree of relationship of ELCAS and performance of the respondents in their English subjects was negatively low correlated, inverse relationship of the ELCAS and performance was found out; and, there was a significant relationship between ELCAS and English performance of the respondents. This means that ELCAS is considered a factor in learning English subject.